The supply chain of bocadillo veleño, a dynamic of regional endogenous development - Medina Rojas, Ivan Dario; Sánchez Parra, Eliana Patricia; Solis Montaño, Yedy (2021)
The internationalization of SMEs contributes to greater productivity and competitiveness, an increase in profits from the use of economies of scale, possibilities for business associations, improvement in research, development and innovation for sustainable growth and competitive positioning (Abubakar, Hand, Smallbone & Saridakis, 2018).